(untitled) (Research, Society and Development, 2020)
Reference evapotranspiration (ETo) is an especially important variable since it is used in the planning and management of irrigation systems and other areas. Therefore, its determination must be made carefully and rigorously in the face of the various existing estimation methods. In this sense, given that the standard Penman-Monteith FAO/56 method requires many meteorological input elements, the study of alternative methods is quite necessary for a view of the numerous delimitations existing in automatic stations in several different regions. The present study aimed to identify, among the methods of Pennan Original, Modified Penman, Blaney-Criddle, Hargreaves-Samani, Priestley-Taylor, and Kimberly Penman, the most alternative methods to the standard model, through statistical analysis of the data, considering the climatic seasons (Summer, Autumn, Winter, and Spring), from three automatic stations located in Cruzeiro do Sul, Porto Walter and Marechal Thaumaturgo in Acre state, Brazil with data belonging to INMET and Xavier, King and Scanlon. It was concluded that the methods of Pennan Original and Kimberly Penman were the ones that best estimated ETo concerning the standard model for the three automatic stations, while the methods of Blaney-Criddle and Hargreaves-Samani presented the worst performance. The Priestley-Taylor method were chosen as alternative to the methods of Pennan Original.